2015
DOI: 10.1002/mus.24946
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound findings of carpal tunnel syndrome in a hunter syndrome patient

Abstract: This case demonstrated unique ultrasound findings in a Hunter syndrome with CTS. Ultrasound also localized the median nerve lesion in the setting of end-stage median neuropathy and nonlocalizing electrophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…8 However, despite absent clinical and neurophysiological differences, vanVeen et al found a significant reduction of the ulnar nerve swelling in the treatment, but not in the placebo group. 1 Treatment, therefore, reduced ulnar nerve edema and inflammation as intended, but it had no effect on clinical symptoms or nerve conduction findings. The study, therefore, clearly shows that in focal neuropathies local corticosteroid injections do not exert their therapeutic effect directly on the peripheral nerve, but probably mainly on surrounding tissues.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…8 However, despite absent clinical and neurophysiological differences, vanVeen et al found a significant reduction of the ulnar nerve swelling in the treatment, but not in the placebo group. 1 Treatment, therefore, reduced ulnar nerve edema and inflammation as intended, but it had no effect on clinical symptoms or nerve conduction findings. The study, therefore, clearly shows that in focal neuropathies local corticosteroid injections do not exert their therapeutic effect directly on the peripheral nerve, but probably mainly on surrounding tissues.…”
mentioning
confidence: 89%
“…We read with great interest the study by Alkhachroum and Preston about ultrasonographic (US) findings of carpal tunnel syndrome (CTS) in the case of a 40-yearold patient affected by mucopolysaccharidosis II. 1 The patient was evaluated by clinical, neurophysiological, and US examinations. He presented with pain and electric shocks in the fingers since childhood, with worsening during the preceding year.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is a case report of an adult MPS II patient with end-stage CTS published by Alkhachroum et al which reveals the same US findings and acknowledges the role of US in identifying the median nerve and its alterations associated with CTS in MPS II patients. [29] A meta-analysis found that the sensitivity and specificity of US in establishing the CTS diagnosis in adults, is 77.6% and 86.8 %, respectively [30].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, neuromuscular ultrasound is well-tolerated and can accurately diagnose CTS, while also providing anatomic visualization to guide management strategies. 8,9 Studies have investigated ultrasound for CTS detection in mucopolysaccharidoses, 6,10,11 but none examined the exclusive use of ultrasound to confirm diagnosis. We present a patient with Hunter syndrome in whom ultrasound alone confirmed CTS and revealed a profound median mononeuropathy.…”
mentioning
confidence: 99%